Синтез похідних імідазоліну – активної основи антикорозійних засобів - Kartun, Igor M.; Kochirko, Bogdan F. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2024)
Synthesis of the active base of a solid corrosion inhibitor for the protection of underground equipment of gas condensate and oil wells, namely, 1-amido-hydroxystearate-diethylenediamine-2-hydroxystearyl-imidazoline and ethylene-bis-2-hydroxystearyl-imidazoline is described. Imidazoline derivatives have been obtained by condensation of triethyltetramine with 12-hydroxystearic acid at different temperatures. Analysis of the reaction products by 1H NMR spectroscopy and chromatography-mass spectrometry is presented, with confirmation of the formation of target products at each stage of synthesis. It was found that when the reaction is carried out at 280 ℃, a significant amount of ethylene-bis-2-hydroxystearyl-imidazoline is formed. The perspective of using a technical mixture of 1-amido-hydroxystearate-diethylenediamine-2-hydroxystearyl-imidazoline and ethylene-bis-2-hydroxystearyl-imidazoline for anti-corrosion protection of oil pipelines is demonstrated.